Pengaruh ukuran perusahaan, leverage, aktivitas, likuiditas terhadap nilai perusahaan pada perusahaan sub sektor makanan dan minuman yang terdaftar di BEI Tahun 2016-2019 - Arisandy Aruan, Deasy; Chrisna Vany Yola Sitorus, Posma; Putri Br. Sinaga, Mayang; Sari, Novita (Jurnal Paradigma Ekonomika, 2022)
This research was conducted to determine the effect of Firm Size, Leverage, Activity, Liquidity, and Firm Value in the Food and Beverage Sub-Sector Companies listed on the IDX 2016-2019. This study used a sample of 13 companies in the food and beverage sub-sector listed on the IDX 2016-2019. This research uses quantitative research. The sampling method is purposive sampling. From the results of this study can be seen partially that firm size has a significant positive effect on firm value, leverage has no significant impact on firm value, activity does not have a substantial impact on firm value, liquidity has no significant impact on firm value. And simultaneously, firm size, leverage, activity, and liquidity significantly affect firm value in the food and beverage sub-sector listed on the IDX 2016-2019.